Renal adenoma in a 5-year-old Labrador retriever: Big is not always bad - Lillakas, Kristina (Canadian Veterinary Medical Association, 2013)
A 5-year-old Labrador retriever was presented with anorexia, hematuria, and a 3-week history of mild lethargy, periodic inappetance, and weight loss. A firm mass in the cranial abdomen was discovered on physical examination. Following clinical work-up the owners elected euthanasia. On postmortem examination, histopathology determined that the mass was a benign renal adenoma.